In-depth imaging of in-vitro tissue models using electrical impedance tomography - Jian Deng; Babu Linkoon P Meenaketan; Saeedeh Ebrahimi Takalloo; Yoke Chin Cha; Tom Torfs; Dries Braeken; Jan De Beenhouwer; Jan Sijbers (e-Journal of Nondestructive Testing)
This study presents a novel micro-electrode-based measurement system designed for in-depth electrical impedance imaging of in-vitro tissue models. Preliminary study regarding the influence of electrode size and density on imaging quality is carried out in this work. In addition to the measurement apparatus, we introduce a memory-efficient imaging technique capable of producing high-resolution 3D electrical impedance (conductivity) reconstruction. The performance of the proposed system is validated through simulations and experimental evaluations, demonstrating its significant potential for advancing biological research, particularly in applications such as organoid and spheroid culturing.